Serapan Hara N, P, K dan Pertumbuhan Tanaman Jagung Pada Berbagai Dosis Pupuk Anorganik dan Organik di Tanah Inceptisol - Mulyati Mulyati; Baharuddin AB; R Sri Tejo Wulan (LPPM Universitas Mataram, 2021)
The use of inorganic fertilizers has an important role in increasing plant growth and production. But it also causes various problems such as decreasing soil organic matter, soil acidity, soil degradation, nutrient imbalance and increasing environmental pollution. Therefore, it needs to be balanced with the provision of organic fertilizers. A field experiment was conducted to study the effect of application of various doses of inorganic and organic fertilizers on N, P, K nutrient uptake and maize plant growth. The experimental design used was a randomized block design arranged in a factorial manner consisting of two factors. The first factor is the dose of inorganic fertilizer (A): 0, 150 and 300 kg ha-1 phonska and the second factor is organic fertilizer plus (P): 0, 10, 20 tons ha-1. The two factors were combined and each treatment combination was repeated three times. The data obtained were analyzed by analysis of variance at the 5% level of significance. The results showed that there was no interaction between the application of inorganic and organic fertilizers on the growth and nutrient uptake of N, P and K. However, the application of inorganic and organic fertilizers had a significant effect on all tested agronomic traits except for plant height. Nutrient uptake of N, P and K also increased significantly due to the application of inorganic and organic fertilizers. The balance of inorganic and organic fertilizer application increases the availability of nutrients as well as the uptake of N, P, and K nutrients by maize plants.